A stochastic model for the dynamics of electromagnetic waves connected to each other on the mirror - A.M. Basharov (Учёные записки Казанского университета: Серия Физико-математические науки)
The paper develops stochastic differential equations serving as the basis for derivation of master equations for microcavity photons pumped with either classic or quantized contracted fields. The interaction operator on the microcavity mirror is derived from the non-resonant field operator interacting with the quantum particle by means of the algebraic perturbation theory, with allowance for various interference processes.